Difference in aqueous concentration and vitreous mass of cytokines in high myopias with and without choroidal neovascularization - Zhang, Shian; Mao, Jianbo; Chen, Nuo; Fang, Yuyan; Chen, Yijing; Zheng, Zicheng; Chen, Yiqi; Shen, Lijun (Frontiers in Medicine, 2022)
Purpose: To investigate and compare the aqueous humour (AH) concentration and vitreous mass of cytokines in high myopias (HM) with and without myopic choroidal neovascularization (mCNV). And the correlations between cytokines and the size of CNVs on optical coherence tomography angiography (OCTA) images were also be analysed. Methods: This observational study included 56 highly myopic eyes with and without CNV and 57 control eyes with cataracts. AH samples were obtained prior to the intravitreal injection of anti-VEGF and cataract surgery. This study measured multiple inflammatory cytokines including VEGF, interleukin (IL)-6, IL-8, IL-10, interferon-inducible protein-10 (IP-10), and monocyte chemotactic protein-1 (MCP-1) by multiplex bead assay. AH cytokine level, axial length, and vitreous volume were used to calculate the vitreous mass of cytokines. Results: The vitreous mass of VEGF in eyes with mCNV was significantly higher than that in control group. However, the difference in AH concentration of VEGF between high myopias with mCNV was not observed. Inflammatory cytokines were upregulated (IL-6, IL-10, and MCP-1) in highly myopic eyes both with and without mCNV (all P<0.05). There was also a significant difference in the vitreous mass of IL-8 and IP-10 among all three groups (P<0.05). Conclusions: We confirmed the secretion of VEGF increased in eyes with mCNV from a new perspective. The development of both HM and mCNV were related to inflammatory cytokines and the upregulation of inflammatory cytokines may precede upregulation of VEGF. The vitreous mass might be tried as a more reliable potential biomarker in eyes with longer axial length.